INCREASING THE ROLE OF THE MEDIATION INSTITUTION IN CONFLICT RESOLUTION - Sherqobilova , Shoxsanam Abduraxmonovna (Educational Research in Universal Sciences, 2023)
In the context of the globalization of modern society, the issue of resolving disputes by mutual alternative agreement is of particular importance. The mediation procedure helps the parties to maintain partnership relations, solve problems in social spheres such as family relations, social sphere, economic sphere, corporate and inter-corporate disputes, financial and banking sector. The article focuses on issues of increasing the role of the mediation institution in conflict resolution.